Anne Frank's Tree Nature's Confrontation with Technology, Domination, and the Holocaust - Katz, Eric (The White Horse Press, 2022)
"In this important and original interdisciplinary work, well-known environmental philosopher Eric Katz explores technology's role in dominating, and thus destroying, both nature and human life and society. Katz's argument innovatively connects two distinct areas: the fundamental goal of the Holocaust, including Nazi environmental policy, to heal the degenerate elements of society; and the plan to heal degraded natural systems that informs the contemporary environmental policy of 'ecological restoration'. In both arenas of 'healing', Katz argues that technology drives action, while domination emerges as the prevailing ideology. Katz's work is a plea for the development of a technology that does not dominate and destroy but instead promotes autonomy and freedom. Anne Frank, a victim of Nazi ideology and action, saw the titular tree behind her secret annex as a symbol of freedom and moral goodness. In Katz's argument, the tree represents a free and autonomous nature. 'Anne Frank's Tree' is rooted in an empirical approach to philosophy, seating complex ethical ideas in a powerful narrative of historical fact and deeply personal lived experience."